Entre práticas e discursos: Gilberto Mendes, Willy Corrêa de Oliveira e o campo da música erudita brasileira pós 1980 - Carla Delgado de Souza (Ciências Sociais Unisinos)
The goal of this paper is to understand how some changes in the Brazilian classical music field since the late 1970s happened, through the analysis of the trajectory of two impor- tant Brazilian composers: Gilberto Mendes and Willy Corrêa de Oliveira. I noticed that a pulverization of aesthetical fights and movements not occurred only in Brazil, but also in the Euroamerican context in that moment. Those alterations were connected to political and aesthetical perceptions. Besides that, the discourse in favor of an approximation of popular artistic creation was present in the creative process of these two composers, in a movement characterized by the musical field as “aesthetical overture” or “post-modernism musical”. Therefore, I seek to demonstrate the process that led to the dissolution of some practices and discourses of important social actors of avant-gard music in the period between 1960 and 1980 in Brazil.